Inventory of the 'lettere e scritture Turchesche' of the Venetian State Archives - Pedani Fabris, Maria Pia.; Bombaci, Alessio, 1914- (Islamic Manuscripts and Books, 2010)
As well as the well-known inventory written by Maria Pia Pedani Fabris in 1994, I \'Documenti Turchi\' dell'Archivio di Stato di Venezia , this book is based on the work by Alessio Bombaci from the 1940s. Pedani's work is an academic inventory of the documents in the archives Lettere e Scritture Turchesche kept in the Venetian State Archives. It describes in detail 822 documents from the first half of the 16th century until the first half of the 17th century. Part of the documents are Ottoman originals, part are Italian translations. They deal above all with commercial affairs. There are name-i hümayun s, but also letters of beylerbeyi s and sancakbeyi s of the Balkan regions and of other lower Ottoman officials.